Presumption of Innocence in Murder Trials: Legal Principles of Circumstantial Evidence in Indonesian Criminal Law - Enggarsasi, Umi (International Journal of Law Reconstruction, 2021)
Murder is one of the most serious criminal offenses with the heaviest penalties in the Indonesian Criminal Code (Kitab Undang-Undang Hukum Pidana/KUHP). Valid evidence is regulated in Article 184 paragraph 1 of the KUHAP, which includes witness statements, expert opinions, documents, exhibits, and the defendant's statements. A judge can only impose a criminal sentence on the defendant with at least two valid pieces of evidence. This research adopts a normative juridical research method with a conceptual and case approach. The data collection method applied is literature research, where literature such as books, notes, and reports from previous studies serves as the primary source of data. In the case of the premeditated murder of Wayan Mirna Salihin, the strength of the circumstantial evidence used in the trial, such as Closed Circuit Television (CCTV) recordings, can be considered weak. This is because the recording does not clearly show or monitor that Jessica Kumala Wongso directly placed cyanide into the Vietnamese iced coffee consumed by the victim. Therefore, the judge should carefully weigh and implement the presumption of innocence principle for the defendant before deciding the case, especially after the discovery of the CCTV evidence.